Integrated Parameters Measurement Of Brushless Direct Current Motor And Control For Quadcopter Application - Leong, Yong Chee (Universiti Sains Malaysia, 2019)
The objective of this project is to measure and study the performance parameters of the BLDC motor. The parameters obtained in this project is propeller thrust, rotor speed and motor current, which is measured by HX711 load cell sensor, A3144 Hall effect RPM sensor and GY-712 Hall effect current sensor respectively. A motor-propeller testbed is set up with the electronic sensor modules and MCU embedded to perform the real-time signal processing in accessing the integrated performance parameters while increasing controlled throttle is applied. On the other hands, step responses of thrust generated by the rotor-propeller are acquired at different fixed throttle inputs. Before conducting the experiment, the sensor modules had been calibrated by comparing the reading with hand measuring tools to validate the accuracy of those sensors and find out that the output of current sensor exist an additional offset of 0.277 A that causing it to deviate from the actual value even though a moving average is applied into current measuring algorithms. The purpose of this experiment is to study the correlations between the measured parameters so as to identify the performance limitations and constraints within the open-loop control system. The results show that the BLDC motor start to toggle on at servo throttle of ‘46’ and reach its maximum throttle at ‘135’ while the motor stalling occurs at throttle percentage of 53.33%. The thrust generated using smaller size propeller is lower however higher rotor speed and lower current consumed is achieved on behalf of that. The step response of thrust at different throttle control is observed in verifying the stability performance of motor-propeller when applying different speeds. The result shows that the motor losing efficiency at high steady throttle or whenever there is a throttle change as the settling time increases and the overshoot occurs in the waste of energy.